Complete amino acid sequence and glycosylation sites of glycoprotein gp71A of Friend murine leukemia virus. - Chen, R (1982)
The complete amino acid sequence of glycoprotein gp71A of Friend murine leukemia virus (F-MuLV) is presented. The protein moiety of gp71A was digested with Staphylococcus aureus (SV8) protease, trypsin, and thermolysin. The sequences of the peptides were determined by the micro dansyl Edman procedure. gp71A is composed of 445 amino acid residues and contains eight oligosaccharide side chains, which are attached exclusively to asparagine by N-glycosyl bonds primarily in the COOH-terminal half of the polypeptide. gp71A is rich in proline (49 residues), tryptophan (16 residues), and cysteine (19 residues). Proline has the highest molar content (11%) of all amino acids. The prolines cluster in two segments. The most interesting one stretches between residue 233 and residue 283 and contains 18 prolines within 51 amino acids. This proline-rich domain most likely forms a flexible polyproline helix. The comparison of gp70 of Moloney murine leukemia virus (Mo-MuLV gp70) with F-MuLV gp71A revealed that 70 amino acids have been exchanged and 9 residues have been deleted from Mo-MuLV gp70. The most striking alterations have taken place within the large polyproline segment (residues 247 to 281). In this part of the molecule 7 amino acids have been deleted in Mo-MuLV and 18 residues have been replaced. This evidence supports the proposal of Shinnick et al. [Shinnick, T. M., Lerner, R. A. & Sutcliffe, J. G. (1981) Nature (London) 293, 543-548] that this area is a "hot spot" for recombination.